Elastic properties of Lochaline sandstone: Numerical experiment vs. measurements - Pervukhina, M.; Shulakova, V.; Lebedev, Maxim; Mayo, S.; Clennell, M.; Gurevich, Boris (EAGE, 2012)
P- and S- velocities of clean quartz Lochaline sandstone are numerically simulated using microtomographic images with resolution of 2 micron and compared with the velocities measured at ultrasonic frequencies. The numerically simulated velocities are in a good agreement with velocities measured at confining pressure of about 30-40 MPa which is high enough to close soft pores but do not cause noticeable deformation of equant pores yet. The obtained results shows that while effects of soft porosity on elastic properties of sandstones cannot be directly simulated from microtomograms, such simulation give reliable results when soft pores are closed.